(untitled) (Bangladesh Journal of Otorhinolaryngology, 2016)
Background: Both elective and emergency tracheostomy as life saving procedure is frequently performed. Tracheostomy can be associated with numerous (per operative and post operative) complications. Methods: this was a cross sectional study 120 patients were studied age ranged from 9 years to 79 years in four different tertiary hospitals in Dhaka from July 2011 to June 2013. Results: Among 120 tracheostomized patients, 75 (62.5%) were patients of emergency tracheostomy group and 45 (37.5%) were patients of elective tracheostomy group. Laryngeal carcinoma and other head-neck malignancy were the common (67.34%) indications for emergency tracheostomy. Maxillofacial and laryngeal surgery (50.1%) was the common indications for elective tracheostomy. Haemmorage was the most common complication. The second most common complication were subcutaneous surgical emphysema and wound infection , Then tube displacement, pericondritis and stomal stenosis/ granulation tissue formation were the complications . In all stages (peroperative, immediate postoperative, early postoperative and late postoperative), the frequency of complications was more in emergency tracheostomy and it was statistically significant (p<0.05). Conclusion: Complications are more in emergency than elective tracheostomy. To reduce complications should be aim of all types of tracheostomy Bangladesh J Otorhinolaryngol; October 2015; 21(2): 69-75